Morphology and properties of polypropylene/ethylene vinyl acetate copolymer/wood powder blend composites (eXPRESS Polymer Letters)
Polypropylene (PP) was blended with ethylene vinyl acetate copolymer (EVA) to form PP/EVA polymer blends. Wood powder (WP) was mixed into these blends at different weight fractions (50/50/0, 45/45/10, 40/40/20, 35/35/30 w/w PP/EVA/WP) to form PP/EVA/WP blend composites. The morphology, as well as thermal and mechanical properties, of these composites were investigated. The scanning electron microscopy (SEM) and differential scanning calorimetry (DSC) results confirm the immiscibility of EVA and PP in the blends, and show that WP is primarily concentrated in the EVA phase. DSC results further show that the EVA crystallization behaviour is significantly influenced by the presence of WP. Dynamic mechanical analysis (DMA) results confirm immiscibility of PP and EVA, as well as an interaction between EVA and WP. Interaction between EVA and WP was further confirmed by Fourier-Transform infrared spectroscopy (FTIR). TGA results show that the blend composite degradation was also influenced by the presence of WP.